2002
DOI: 10.2172/15001166
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Vadose Zone Sediment: Uncontaminated RCRA Borehole Core Samples and Composite Samples

Abstract: Table 2.1. Stratigraphy of the Vadose Zone Beneath the SX Tank Farm. Stratigraphic Symbol (a) Formation Facies/Subunit Description Genesis Holocene/Fill NA Backfill Poorly sorted gravel to medium sands and silt derived from the Hanford formation (Price and Fecht, 1976a) Anthropogenic Unit H1a-gravelly sand Upper coarse-grained sequence equilvalent to Johnson et al.'s (1999) "Hanford Gravel Unit B" and Sobczyk's (2000) "Hanford Unit B" H1a Unit H1a-slightly silty sand Upper fine sand and silt sequence. Equivale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
139
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(163 citation statements)
references
References 1 publication
(1 reference statement)
22
139
2
Order By: Relevance
“…The gravel-dominated HFGD unit is the coarsest in composition, ranging from 63.2% gravel and 36% sand, to 3% gravel and 92% sand at the contact with the finer-grained lower HFSD2 unit (94-98% sand). The silt and clay contents were highest in the Cold Creek units (38.6%), whereas the Ringold Formation is predominantly sand and silt (Serne et al, 2002).…”
Section: Site Descriptionmentioning
confidence: 92%
See 4 more Smart Citations
“…The gravel-dominated HFGD unit is the coarsest in composition, ranging from 63.2% gravel and 36% sand, to 3% gravel and 92% sand at the contact with the finer-grained lower HFSD2 unit (94-98% sand). The silt and clay contents were highest in the Cold Creek units (38.6%), whereas the Ringold Formation is predominantly sand and silt (Serne et al, 2002).…”
Section: Site Descriptionmentioning
confidence: 92%
“…Borehole 299-W22-48 (71.6 m) was drilled in the 200 West area in order to characterize the back- ground geochemistry and the geology of the area proximal to contaminated zones. The volumetric water content (h) and corresponding lithology (measured by Serne et al (2002)) are shown in Fig. 2.…”
Section: Site Descriptionmentioning
confidence: 99%
See 3 more Smart Citations